RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PROYEK KONSTRUKSI BERBASIS WEB PADA UD. SURYA AGUNG - Gabriel, Gino; -, Yulia; Dewi, Lily Puspa (Jurnal Infra, 2014)
UD. Surya Agung is a company focused on in contracting which serve various kinds contractor such as house, factory, advertising board, road construction, bridge, and etc. In the current working system project started from costing budget plan, work scheduling, record every payment information on UD. Surya Agung still using manual system such as use microsoft word. More over to get the processing project information from outer city or outer island can be only know by call or survey the location. Based on the background problems on UD. Surya Agung. Authors designed a system information management project software to store every information in a project that can overcome the problems . The software build using PHP as programming language, PostgreSQL as database, and Yii Framework as Framework. The result obtained from applications is the manual system on the company can all be store in databse. Cost control and time control can be more accurate. Costing profit or loss account for revenue and payment can be more correctly and accurate.